Chıld Abuse and Neglect: Strategy for the Ten-Year Target “INSPIRE” Goes Beyond the “Check-List”? Is There “Hope”? to “Be” Hopeful? - Saka, Naile Esra; Çelik, Cemil; Ata, Uğur (The Bulletin of Legal Medicine, 2024)
Child abuse and neglect (CAN) is the exposure of a child in the 0-18 age group to a harmful, non-accidental and preventable behavior by the person or persons responsible for caring for him/her at home or in an institution with which he or she interacts. The fact that countries adhere to their own cultural norms and have differences in legislation regarding the adoption of internationally accepted common definitions has made epidemiological studies difficult and has brought about many deficiencies in the prevention and intervention phase of the CAN problem. World Health Organization, UNICEF, UNESCO, the United Nations Secretary-General’s Special Representative on Violence Against Children and the Global Partnership to End Violence Against Children have compiled seven principles called INSPIRE, which will include a forward 10-year period with national development targets, titled “Global Status Report on Preventing Violence Against Children 2020”. A based strategic plan has been developed. According to preliminary data collected from countries, most countries have taken some steps, but the efforts of government officials are reported to be insufficient to achieve sustainable development goals. To bring a universal regulation to combat and intervention methods against CAN; INSPIRE, which draws attention to the importance of health, law, education and social policies, is both hopeful and valuable with its ten-year action plan between 2020-2030 and its recommendations for the need for urgent action.